2013
DOI: 10.4414/smw.2013.13776
|View full text |Cite
|
Sign up to set email alerts
|

Cancer, meta-analysis and reporting biases: the case of erythropoiesis-stimulating agents

Abstract: Reporting and publication bias is a well-known problem in meta-analysis and healthcare research. In 2002 we conducted a meta-analysis on the effects of erythropoiesis-stimulating agents (ESAs) on overall survival in cancer patients, which suggested some evidence for improved survival in patients receiving ESAs compared with controls. However, a meta-analysis of individual patient data conducted several years later showed the opposite of our first meta-analysis, that is, evidence for increased on-study mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…implications Failure to report pre-specified outcomes can seriously bias published evidence [26], especially because positive findings are more likely to be reported than negative findings [17]. For instance, a meta-analysis of cancer trials suggested that administration of erythropoiesis-stimulating agents prolonged survival, while an updated individual patient data meta-analysis that included previously unpublished outcome data showed no significant effect [27].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…implications Failure to report pre-specified outcomes can seriously bias published evidence [26], especially because positive findings are more likely to be reported than negative findings [17]. For instance, a meta-analysis of cancer trials suggested that administration of erythropoiesis-stimulating agents prolonged survival, while an updated individual patient data meta-analysis that included previously unpublished outcome data showed no significant effect [27].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A target hemoglobin level of 11-12 g/dl was associated with the greatest reduction in CRF and improvement in other quality-of-life outcomes (Eton & Cella, 2011). Although ESAs are generally well tolerated, the use of these agents specifically for the management of fatigue must be considered in light of safety issues, including an elevated risk for thromboembolic complications and decreased survival, particularly when ESAs are used in patients with cancer who are not receiving chemotherapy Bormanis et al, 2013;Boulaamane et al, 2013;Gao, Ma, & Lu, 2013;Tonia et al, 2012;Tonia, Schwarzer, & Bohlius, 2013;Wauters & Vansteenkiste, 2012). National clinical practice guidelines (Lichtin, 2011;NCCN, 2015;Rizzo et al, 2010) and the recommendations of the U.S. Food and Drug Administration (2013) should guide decisions about treatment initiation, discontinuation, monitoring, and management in patients receiving ESAs.…”
Section: Benefits Balanced With Harmsmentioning
confidence: 99%
“…Let's take the example of erythropoetin-stimulating agents (ESAs), which were licensed in the early 1990s for treating anemia in cancer patients and became widely used. Early published clinical studies and meta-analyses appeared to show a benefit of ESAs on mortality [11] . It is now known, however, that ESAs actually increase thromboembolic events, cardiovascular events, and overall mortality in cancer patients [12] ; disturbingly, knowledge of this risk was delayed by a decade because of publication and reporting biases [11] .…”
Section: Design and Reporting Biasesmentioning
confidence: 99%